Characterization of swine leukocyte antigen alleles and haplotypes on a novel miniature pig line, Microminipig. (13th August 2014) - Ando, A.; Imaeda, N.; Ohshima, S.; Miyamoto, A.; Kaneko, N.; Takasu, M.; Shiina, T.; Kulski, J. K.; Inoko, H.; Kitagawa, H.
Summary Microminipigs are extremely small‐sized, novel miniature pigs that were recently developed for medical research. The inbred Microminipigs with defined swine leukocyte antigen (SLA) haplotypes are expected to be useful for allo‐ and xenotransplantation studies and also for association analyses between SLA haplotypes and immunological traits. To establish SLA‐defined Microminipig lines, we characterized the polymorphic SLA alleles for three class I (SLA‐1, SLA‐2 and SLA‐3) and two class II (SLA‐DRB1 and SLA‐DQB1) genes of 14 parental Microminipigs using a high‐resolution nucleotide sequence‐based typing method. Eleven class I and II haplotypes, including three recombinant haplotypes, were found in the offspring of the parental Microminipigs. Two class I and class II haplotypes, Hp‐31.0 (SLA‐1*1502–SLA‐3*070102–SLA‐2*1601) and Hp‐0.37 (SLA‐DRB1*0701–SLA‐DQB1*0502), are novel and have not so far been reported in other pig breeds. Crossover regions were defined by the analysis of 22 microsatellite markers within the SLA class III region of three recombinant haplotypes. The SLA allele and haplotype information of Microminipigs in this study will be useful to establish SLA homozygous lines including three recombinants for transplantation and immunological studies.